Legislative and Strategic Framework for Agricultural Sector in The European Union - Vlatka BILAS; Sanja FRANC; Lana TRIFUNIĆ (Communications of International Proceedings, 2021)
The European Union recognizes the importance and fragility of agriculture and farming and therefore, it continuously provides political and strategic framework and measures to facilitate and promote this sector. The common agricultural policy of the European Union (CAP) represents the cornerstone of European Union strategic framework for supporting agriculture development. The aim of this paper is to analyse and synthesize the main elements of the EU common agricultural policy with the purpose of identifying and systemizing key measures and segments covered by the sectoral regulation. Additionally, the strategic and legislative framework for the agricultural sector development in the Republic of Croatia is analysed as a good practice example within the EU.
Keywords: EU; Strategic Framework; Common Agricultural Policy.